Representaciones sobre las lenguas de un grupo de estudiantes indígenas en un programa de formación de docentes de idiomas - Arismendi, Fabio Alberto; Ramirez, Denis; Arias, Sara (Colombian Applied Linguistics Journal, 2016)
Few studies have explored the foreign language learning processes of indigenous students in Colombia. In this article, we present preliminary findings of a research project which aims to explore the challenges that indigenous students face when learning languages in a public university. Based on the theory of social representations, we focus in this text on the representations that participant students have regarding their mother tongue as well as the languages they study, English and French. We carried out a qualitative case-study in which eight students from different ancestral communities participated. Data gathered from individual and collective interviews, class observations and focus groups allowed us to uncover the linguistic repertoires of participants as well as the representations they have of their mother tongue and foreign languages. Findings show that teachers play an important role in the construction of representations and that these evolve throughout the learning process.